PROFESSIONAL COMMUNICATION IN THE DIGITAL AGE: BENEFITS AND CHALLENGES OF USING INSTANT MESSAGING APPLICATIONS IN THE WORKPLACE - Indah Sulistiani; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Professional communication in the digital age increasingly relies on the use of instant messaging applications that provide convenience and efficiency in exchanging information in the work environment. This article discusses the significant benefits of using instant messaging applications, including real-time communication, increased work efficiency, and cross-location collaboration that strengthens team connectivity. On the other hand, the use of these applications also presents challenges such as data security and privacy issues, disruption of concentration due to notifications, and difficulties in information management. Faced with these challenges, a wise approach is needed, prioritising best practices in digital security, time management, and communication ethics to optimise benefits without neglecting the risks involved.